2004
DOI: 10.2169/internalmedicine.43.379
|View full text |Cite
|
Sign up to set email alerts
|

QT Dispersion Correlates with Systolic Rather than Diastolic Parameters in Patients Receiving Anthracycline Treatment

Abstract: Objective The aim of this study was to investigate the relation of QT dispersion to left ventricular (LV) systolic and diastolic function in patients undergoing anthracycline therapy.Methods We used echocardiography to evaluate LV systolic and diastolic function and electrocardiography to evaluate QT dispersion and corrected QT dispersion (QTcD) in patients with hematological diseases, who received anthracycline therapy.Patients Seventy-two patients with hematological diseases who were receiving anthracycline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…Previous studies have shown that QT dispersion was associated with LV dilation [22]. As our patients with SCD had an increased ventricular diameter compared with healthy controls, the increase in QT dispersion in our patients may be partially due to ventricular dilation.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have shown that QT dispersion was associated with LV dilation [22]. As our patients with SCD had an increased ventricular diameter compared with healthy controls, the increase in QT dispersion in our patients may be partially due to ventricular dilation.…”
Section: Discussionsupporting
confidence: 49%
“…The relationship between myocyte dysfunction and arrhythmogenesis in cancer cardiotoxicity is not completely determined; however, an investigation by Nakamae et al 61 of 72 adults receiving anthracycline therapy suggests a link between these problems. In that study, the QTc interval during anthracycline therapy correlated moderately well with the degree of LV enlargement (r=0.…”
Section: Arrhythmias and Qt Interval Prolongationmentioning
confidence: 99%
“…Nevertheless, assessment of the QT interval may help identify patients at higher risk for cardiotoxicity. 61 Echocardiography is likely to continue to be the mainstay of monitoring, given that it is portable, is widely available, causes minimal pain, can usually be performed without sedation, and provides real-time data. The utility of echocardiography currently extends beyond the traditional measures of LV shortening and ejection fractions.…”
Section: Monitoring Cardiac Structure and Function During Therapymentioning
confidence: 99%
“…Retrospective examination of cardiac tissue from patients treated with anthracyclines found myocardial necrosis, fibrosis, and myocytolysis. 129 A report by Nakamae et al 130 provided evidence of correlation between QTc interval increase, left ventricular dilation, and systolic dysfunction in patients treated with anthracycline. More than 20% of patients treated with anthracyclines experienced substantial degrees of heart failure.…”
Section: Anthracyclinesmentioning
confidence: 99%